2009
DOI: 10.1111/j.1751-7893.2009.00114.x
|View full text |Cite
|
Sign up to set email alerts
|

Intervention to improve level of overall functioning and mental condition of adolescents at high risk of developing first‐episode psychosis in Finland

Abstract: JERI-type intervention may improve level of overall functioning and support mental condition in adolescents at risk of developing first-episode psychosis, even though further study with larger numbers of subjects, with a control group and with a longer follow-up time, is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 21 publications
0
26
0
1
Order By: Relevance
“…The team had three main tasks: first, to identify the possible risk of developing psychosis among help‐seeking adolescents using self‐report screening tools and an interview; second, in such cases, to meet frequently with the client and family together with the community co‐worker to find a way to reduce stress and support the client in his or her overall functioning at school or at work; and third, if some other severe psychiatric disorder or untreated psychosis should emerge, to guide the subject to adequate psychiatric care. The detection and intervention model was developed originally at Jorvi Hospital in HUCH between the years 2006 and 2008 (Granö et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The team had three main tasks: first, to identify the possible risk of developing psychosis among help‐seeking adolescents using self‐report screening tools and an interview; second, in such cases, to meet frequently with the client and family together with the community co‐worker to find a way to reduce stress and support the client in his or her overall functioning at school or at work; and third, if some other severe psychiatric disorder or untreated psychosis should emerge, to guide the subject to adequate psychiatric care. The detection and intervention model was developed originally at Jorvi Hospital in HUCH between the years 2006 and 2008 (Granö et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…() reported that mood and anxiety disorders were present in 39.1% of those cases treated in secondary mental health care before the onset of psychosis. Finally, in intervention studies of those in an at‐risk state for psychosis, there is a tendency for the level of anxiety to reduce during treatment (Addington et al., ; Granö et al., ; Marshall et al., ), suggesting that different anxiety symptoms are present when in an at‐risk state for psychosis.…”
Section: Introductionmentioning
confidence: 99%
“…Subjects in this study consist of clients at an early intervention team JERI (Jorvi Early psychosis Recognition and Intervention) in southern Finland (Granö et al, 2009). The team met adolescents between ages 11 and 23 in their natural surroundings (e.g., at school or at home), together with their parents and with a community co-worker who originally contacted the JERI team because their client had newly occurred and unclear mental health problems.…”
Section: Subjectsmentioning
confidence: 99%
“…Th e detection and intervention model of the JERI team was originally developed in Finland at HUCH Jorvi Hospital between 2006and 2008(Gran ö et al 2009). …”
Section: Subjectsmentioning
confidence: 99%